GENOTYPIC RESPONSE ON GROWTH AND YIELD IN PAPAYA - D. K. VARU; K. D. PATEL; SANDIP MAKHMALE (The Bioscan, 2020)
The present investigation was undertaken to study the genetic variability of 9 genotypes of papaya along with Pusa Dwarf as a check for various horticultural characters. Fruit yield is the main trait commercially useful to the farmers. The number of fruits and fruit yield per plant were recorded significantly highest (36.38 and 33.81 kg/ pl. and 84.52 t/ha, respectively) in genotype selection-4. Significantly highest fruit length and weight (25.02 cm and 1832 g) were noted in Selection-6, whereas, highest fruit girth (47.3 cm) was noted in Pusa Dwarf but was observed at par with Selection-4. While, the highest pulp weight (1327.93 g ) and pulp seed ratio (1230.56) were noted in Selection-4, but highest pulp-peel ratio (5.74) was noted in Selection-8. In case of growth, bearing and plant height have also a great role to check the lodging of plants which were performed better (59.42 and 148.16 cm, respectively) in Pusa Dwarf but, highest stem girth (38.40 cm) in Selection-6 which were observed at par with Selection-4.